Actuator model for spacecraft attitude control simulation. Issue 4 (8th April 2021) - Zhang, Chengxi; Wu, Jin; Sun, Ran; Wang, Mingjiang; Ran, Dechao
Abstract : Purpose: The purpose of this paper is to study the general actuator modeling in spacecraft attitude control systems. Design/methodology/approach: The proposed module in this paper provides various non-ideal factors such as the second-order dynamic time response, time-delay, bias torques, dead-zones and saturation. The actuator module can make the simulation as close to the practical situation as possible. Findings: This paper presents a practical integrated module for the simulation of attitude control algorithms. Based on theoretical modeling, we give simulation modules and numerical examples. The proposed model can be directly used in spacecraft control simulation. Instead of considering only a few of them, it makes the simulation more convincing. Though it may not be perfect, it is better than totally ignoring the actuator dynamics. Originality/value: The authors provide an integrated actuator model for spacecraft attitude control simulation, considering as many nonlinear factors as possible once time.